Answer:
Therefore the Final Solution is
x = 2 and y = 4
( 2 , 4 )
Explanation:
Given:
...............Equation ( 1 )
................Equation ( 2 )
To Find:
x = ?
y = ?
Solution:
Substitute Equation ( 1 ) in Equation ( 2 ) we get
![x=-2x+6\\\\3x=6\\\\3x=6\\\\x=(6)/(3) \\\\\therefore x =2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vfysi6t6hx5tpzbgesq4pl7s1g2rnvmzif.png)
Now Substituting x = 2 in Equation ( 1 ) we get
![y =2* 2\\\\\therefore y=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8qmdlj3ej7kvp8fefk2i7tylvt0sthkxmw.png)
Therefore the Final Solution is
x = 2 and y = 4
( 2 , 4 )